Measures of Relative and Absolute Convergence and Pro-poor Growth with an Illustration based on China (2010–2018). - Bárcena-Martín, Elena María; Silber, Jacques; Zhang, Yuan (Wiley, 2024)
Income mobility is a key issue for understanding the process of economic growth and distributional change. Some economists have used the concept of “pro-poor growth” to examine, with individual-level panel data, whether the poor benefit more than the rich from economic growth by tracking the extent of income mobility among different population subgroups. There is also literature in macroeconomics on the measurement of convergence. This paper introduces population-weighted relative and absolute indices of mobility, convergence, and pro-poor growth; it also distinguishes between anonymous and nonanonymous approaches to these issues. The empirical analysis is based on Chinese panel data for the period 2010–2018. In both absolute and relative terms, income growth in China was greater for individuals with an initially lower income but only for lower income deciles in relative terms. There was also an overall increase in individual welfare from anonymous and nonanonymous perspectives, which was higher among younger individuals. The welfare of the poor did not increase more than that of the nonpoor. These results shed light on the evolution of income distribution in China during the past decade's rapid economic growth.
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/856
Keywords: Movilidad social; Desarrollo económico y social; Convergencia (Economía); Anonymous and nonanonymous approach; Convergence; Exchange and structural mobility; Pro-poor growth